MULTIPLE STREAMS FRAMEWORK IN REGIONAL DEVELOPMENT AGENDA SETTING: THE CASE OF ECONOMIC SELF-SUFFICIENCY IN WEST SULAWESI PROVINCE, INDONESIA - APRILIA, YUYUN; HANS, AMRIL (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Regional economic self-sufficiency represents a critical development priority in decentralized governance systems, yet understanding how this issue ascends to formal policy agendas remains theoretically and empirically underexplored. This study examines the agenda setting dynamics through which economic autonomy emerged as a strategic priority in subnational medium-term development planning, applying qualitative case study methodology to analyze policy formulation processes. Data were collected through semi-structured interviews with planning agency officials, document analysis of development plans and regulatory frameworks, and non-participant observation of coordination meetings during May-June 2025. Findings reveal that agenda prioritization resulted from convergence of three independent policy streams: the problem stream established urgency through compelling evidence of non-inclusive economic growth (4.83% GDP expansion alongside 10.41% poverty rates), severe fiscal dependency (72% central transfer reliance with minimal local revenue generation), and structural deficiencies in human capital and infrastructure quality; the policy stream generated feasible solutions through evidence-based planning processes producing an innovative five-pillar development framework emphasizing economic diversification, sectoral integration, and sustainability; while the political stream provided legitimacy through harmonious executive-legislative relations, leadership commitment, and transparent deliberation mechanisms. Stream coupling occurred during scheduled planning periods, creating policy windows enabling issue elevation from recognized problems to formal priorities. Results demonstrate that successful agenda setting in decentralized contexts requires not only stream convergence but also vertical coordination ensuring subnational policies align with national frameworks while addressing local needs. The study extends agenda setting theory to subnational governance in developing countries, revealing that political consensus significantly enhances coupling effectiveness. Practically, findings emphasize that achieving formal agenda status represents only an initial step; sustained implementation capacity and adaptive monitoring systems are essential for translating priorities into tangible development outcomes.